ALRT‐based energy detection using uniform noise distribution. Issue 9 (26th February 2015) - Wang, Kezhi; Chen, Yunfei; Chen, Jiming
Abstract: Energy detection is widely used in cognitive radio due to its low complexity. One fundamental challenge is that its performance degrades in the presence of noise uncertainty, which inevitably occurs in practical implementations. In this work, three novel detectors based on uniformly distributed noise uncertainty as the worst‐case scenario are proposed. Numerical results show that the new detectors outperform the conventional energy detector with considerable performance gains. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Three novel detectors based on uniformly distributed noise uncertainty as the worst‐case scenario are proposed in this paper. Numerical results show that even when there is a mismatch between the assumed uniform distribution and the actual distribution of the noise power, the new schemes still have considerable performance verifying the robustness of the new schemes.